Pengaruh Kenyamanan Pemakaian Alat Pelindung Diri (APD) terhadap Kinerja Profesional Pemberi Asuhan (PPA) Kamar Bedah di RS Kota Padang Pada Masa Pandemi Covid-19 - Leo Agustigno; Yulastri Arif; Mira Susanti; Rahmi Fahmy; Zifriyanthi Minanda Putri; Dewi Murni (Universitas Batanghari Jambi, 2022)
The vulnerability of COVID-19 transmission for Caregiver Professionals (PPA) who work in hospitals requires efforts to prevent it. One of the efforts implemented is the use of Personal Protective Equipment (PPE). However, the comfort of wearing PPE has an influence on the performance of PPA in the hospital, especially the performance of PPA who works in the operating room. This influence starts from the dimensions of work quality performance, work quantity, work timeliness, effectiveness, work independence and work interpersonal relationships. The purpose of this study was to determine whether there was an effect of the convenience of using personal protective equipment (PPE) on the performance of the surgical care provider (PPA) in the Padang City Hospital during the Covid-19 pandemic. This research is a quantitative research with Cross Sectional method. The population in this study is PPA who work in operating rooms and provide services to COVID-19 surgical patients, totaling 252 people and the research sample as many as 155 people. The instrument in this study used a questionnaire on Convenience of Using Personal Protective Equipment Covid-19, Factors that Affect the Comfort of PPE and Performance During Use of Personal Protective Equipment. Test method Data collection with frequency distribution analysis using SPSS and SEM analysis PLS 3.0. The results showed that there were 5 factors that were significantly related to the use of PPE, namely effectiveness, interpersonal, independence, quantity and working time with p-values of each (sig value) < 0.05, namely 0.001, 0.000, 0.000,0.000, 0.012 and One factor that is not significantly related is the quality of work with a p-value (sig value 0.066 > 0.05.